Method of prizes determine on additional services which are available for passengers in railway stations and trains - Piatyhorets, H. S. (Science and Transport Progress, 2011)
The order of drafting of calculations on the additional services given to passengers at train stations is considered; a procedure of calculation of the direct charges is offered.